2019
DOI: 10.1161/circheartfailure.119.006125
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the Cardiovascular Physical Examination and Impact of Spironolactone in Heart Failure With Preserved Ejection Fraction

Abstract: Background: The prognostic value of physical examination, its relation to quality of life (QoL), and influence of therapy in heart failure with preserved ejection fraction (HFpEF) is not well known. Methods and Results: We studied participants from the Americas with available physical examination (jugular venous distention, rales, and edema) at baseline in TOPCAT (Treatment of Preserved Cardiac Function Heart Failure with an Aldosterone Antagonist). The association of the number of signs of congestion with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…Diagnosing is rendered more challenging by the presence of several comorbidities that may confound the diagnosis or be alternative causes of symptoms, as well as lack of proven biomarker thresholds or echocardiographic parameters. The diagnosis can be even more difficult among outpatients without frank pulmonary edema or jugular distention, but more subtle and less specific symptoms and signs such as dyspnea on exertion and edema (28). Accordingly, classifying HFpEF in such patients varies across studies.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosing is rendered more challenging by the presence of several comorbidities that may confound the diagnosis or be alternative causes of symptoms, as well as lack of proven biomarker thresholds or echocardiographic parameters. The diagnosis can be even more difficult among outpatients without frank pulmonary edema or jugular distention, but more subtle and less specific symptoms and signs such as dyspnea on exertion and edema (28). Accordingly, classifying HFpEF in such patients varies across studies.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we assessed whether lowered SUA was associated with reductions in outcomes by simultaneously entering baseline and time-updated SUA into semiparametric or Cox models as appropriate with all outcomes, as employed previously. 23,24 Analyses were performed using STATA Version 14.0 (StataCorp LLC, College Station, TX, USA). A two-sided P-value of <0.05 was considered to indicate a difference of statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, probable beneficial effects of these drugs in HFpEF patients were observed from different studies. For instance, in the TOPCAT trial, spironolactone (one of the MRAs) was reported to reduce congestion in HFpEF patients [38]. In the CHARM-preserved trial, candesartan (one of the ARBs) was shown to reduce HF admissions in HFpEF patients [39].…”
Section: The Challenges Of Hfref and Hfpefmentioning
confidence: 99%